2015
DOI: 10.3390/ijms17010047
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Target Therapies Are Able to Block the Inflammation Associated with Dysfunction of the Cholesterol Biosynthesis Pathway

Abstract: Abstract:The cholesterol pathway is an essential biochemical process aimed at the synthesis of bioactive molecules involved in multiple crucial cellular functions. The end products of this pathway are sterols, such as cholesterol, which are essential components of cell membranes, precursors of steroid hormones, bile acids and other molecules such as ubiquinone. Several diseases are caused by defects in this metabolic pathway: the most severe forms of which cause neurological involvement (psychomotor retardatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 143 publications
0
10
0
Order By: Relevance
“…Cholesterol is recognized as the main modulator of cell membranes phospholipid composition. It is also well known that the content of cholesterol may vary under different pathological conditions [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Cholesterol is recognized as the main modulator of cell membranes phospholipid composition. It is also well known that the content of cholesterol may vary under different pathological conditions [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these forms of “systemic” hypocholesterolemia, there can be “tissue” hypocholesterolemias, such as in patients with inherited defects in cholesterol biosynthesis [97], where circulating cholesterol is normal or slightly low but brain cholesterol can be virtually absent. This is due to the fact that all the cholesterol contained in the brain is the result of an in situ synthesis because the blood-brain barrier does not allow the passage of circulating lipoproteins [98,99,100]. Therefore, when there is a defect in cholesterol biosynthesis and cholesterol synthesis is impaired, intermediate metabolites accumulate in the central nervous system and cause apoptosis, autophagy, and NLRP3-inflammasome activation [97,100,101,102] (Figure 3), leading to neuroinflammation [98,99,103].…”
Section: Effects Of Cholesterol On the Innate Immune System And Itmentioning
confidence: 99%
“…This is due to the fact that all the cholesterol contained in the brain is the result of an in situ synthesis because the blood-brain barrier does not allow the passage of circulating lipoproteins [98,99,100]. Therefore, when there is a defect in cholesterol biosynthesis and cholesterol synthesis is impaired, intermediate metabolites accumulate in the central nervous system and cause apoptosis, autophagy, and NLRP3-inflammasome activation [97,100,101,102] (Figure 3), leading to neuroinflammation [98,99,103]. The damage to the central nervous system presents with psychomotor retardation, developmental delay, structural brain malformations, multiple congenital anomalies, microcephaly, autism and other behavioral disorders [97].…”
Section: Effects Of Cholesterol On the Innate Immune System And Itmentioning
confidence: 99%
“…Although there is increasing evidence of the link between mitophagy and the inflammasome in human health and disease [ 1 , 17 , 121 , 122 , 123 ], few studies have reported the key components through which mitophagy regulates the inflammasome and vice versa. The interrelationship between inflammasome and mitophagy is summarized in Figure 3 .…”
Section: Mitophagy Crosstalk With the Inflammasomementioning
confidence: 99%
“…In the context of cardiovascular diseases, dysregulation of the cholesterol pathway leads to mitochondrial dysfunction and ROS production, which are related to defective autophagy/mitophagy and further activation of the NLRP3 inflammasome [ 122 ]. Lipid-activated eukaryotic initiation factor 2 α (eIF2α) signaling suppresses Parkin-mediated mitophagy, and reduces mitochondrial damage and inflammasome activation [ 158 ].…”
Section: Altered Crosstalk Between Inflammasome and Mitophagy In Tmentioning
confidence: 99%